The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/medicina57060611
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Healthcare Professionals to Get Vaccinated against COVID-19 Two Weeks before Initiation of National Vaccination

Abstract: Background and Objectives The greatest challenge vaccines face is that of acceptance from the general population. Healthcare professionals’ (HCPs) recommendations have significant influence on general public vaccination behavior. The aim of this study was to assess the willingness of HCPs to get vaccinated against COVID-19, two weeks before initiation of vaccinations. Materials and Methods: We conducted an anonymous online survey from 11–15 December 2020 among HCPs by emails delivered from the local medical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
0
11
0
4
Order By: Relevance
“…This is not surprising given the fact that the students represented the vast majority of the sample. The major concern regarding the perceived lack of efficacy reinforces previous reports on respondents who had doubts about the performance of the vaccine [13][14][15][16][17][18][19]. This large group of participants allowed to identify the most commonly reasons that contributed to respondents' decisions on COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 68%
“…This is not surprising given the fact that the students represented the vast majority of the sample. The major concern regarding the perceived lack of efficacy reinforces previous reports on respondents who had doubts about the performance of the vaccine [13][14][15][16][17][18][19]. This large group of participants allowed to identify the most commonly reasons that contributed to respondents' decisions on COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 68%
“…Regardless of the fact that more evidence emerged showing the safety of the COVID-19 vaccine, a certain percentage of the population still exhibit fear of post-vaccination side effects [33,34]. Vaccine hesitancy was especially apparent during the initial stage of the vaccination programs [61]. This attitude is maintained despite the evidence-based data confirming the safety and effectiveness of anti-COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings of the present study, Roy et al 13 found that the top reasons for reluctance were long- and medium-term safety concerns and concerns over the clinical trial’s exclusion of specific groups. Furthermore, Pataka et al 29 found that the rate of acceptance of COVID-19 vaccine was higher in healthcare professionals working with COVID-19 patients and also among physicians (76.5%) compared with nurses (48.3%) and other healthcare professionals. According to Unroe et al, 30 concern about side effects was the primary reason for vaccine hesitancy (70%).…”
Section: Discussionmentioning
confidence: 99%